1987
DOI: 10.1107/s0108768187098355
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the distortion of the tetrahedra in acid phosphate groups H n PO4 (n = 1–3) on hydrogen-bond length

Abstract: The distortions of the PO4 tetrahedra of acid phosphate groups HnPO4 (n = 1-3) have been studied by examining the correlations of the P-O bond lengths,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…The constancy of the average Y--O distance in XO4 ions is well known (cf. Baur, 1974;Ichikawa, 1987Ichikawa, , 1988. In the present compound there is an excellent agreement among the mean Sc O distances at the three temperatures after riding-model correction (Table 3).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The constancy of the average Y--O distance in XO4 ions is well known (cf. Baur, 1974;Ichikawa, 1987Ichikawa, , 1988. In the present compound there is an excellent agreement among the mean Sc O distances at the three temperatures after riding-model correction (Table 3).…”
supporting
confidence: 66%
“…Baur, 1974;Ferraris & Ivaldi, 1984); ideally the X atom is shifted from the centre of the oxygen tetrahedron, while retaining site symmetry 3m (Ichikawa, 1987(Ichikawa, , 1988. This leads to three larger and three smaller O--X--O angles.…”
mentioning
confidence: 99%
“…Figure 8a and c can be compared to Fig. 1 of Ichikawa (31), in which similar results of PO (OH) groups are presented. In Fig.…”
Section: Hydrogen-bond Geometrymentioning
confidence: 62%
“…It was noted at that time, however, that while Ichikawa (31), in his examination of bond distances in phosphates, differentiated between PO groups with differing numbers of donor oxygen atoms, Catti et al (32) made no such distinction between different types of SO groups in their study of S-OH distances. Moreover, Ichikawa demonstrated that P-O bond lengths (that is, the bonds between phosphorus and non-hydrogen bonded oxygen atoms) in PO (OH), for example, are also correlated to O " 2O distances, as a result of the influence of the latter on P-O " bond lengths and the tendency for the phosphate ion to maintain a constant average value of all four phosphorous-oxygen distances, Fig.…”
Section: Hydrogen-bond Geometrymentioning
confidence: 96%
“…Table 4 clearly shows that the bond distances and angles in Se(1)O4 shift in such a way as to reduce the distortion and those in Se(2)O4 shift so as to increase the distortion. As a result the dimer has a net dipole moment, since the deviation of the Se atom from the center of the O atoms is larger in HSeO4 than in SeO4 (Ichikawa, 1987(Ichikawa, , 1988. The dipole moment vectors lie in the mirror plane, but they are arranged antiparallel along the a axis, parallel along the b axis, and antiparallel to each other between two adjacent arrays of the dipole-moment vectors in the (100) plane.…”
Section: Selected Bond Distances (A) and Angles (°)mentioning
confidence: 99%